The Effect of Social Support on Volunteers’ Task Effectiveness and Satisfaction - Kurnianingsih, Sri (Universitas Negeri Semarang, 2015)
Community-based early child education group (PosPAUD) is part of government strategy to increase the access of early child education service in Indonesia. This activity is community-based activities that surrender to volunteers. Sustainability of the activity becomes the hardest part to be achieved. The objective of this study is to find out the effect of social support on volunteers’ task effectiveness and satisfaction that led to sustainability. Subject of this research are 442 volunteers of early child education groups in Central Java. The data is collected through questionnaire. The result has shown that there is a significant correlation at the 0,01 level among social support and task effectiveness and satisfaction.How to citeKurnianingsih, S. (2015). The Effect of Social Support on Volunteers’ Task Effectiveness and Satisfaction. Indonesian Journal Of Early Childhood Education Studies, 4(1), 26-29. doi:10.15294/ijeces.v4i1.9449